Rediscovery of the Tamaulipas white-sided jackrabbit (Lepus altamirae) after a century from its description - Silva-Caballero, Adrián; Rosas-Rosas, Octavio Cesar (Therya Notes, 2022)
The Tamaulipas white-sided jackrabbit, Lepus altamirae, was originally described as a subspecies of Lepus merriami more than a century ago. Several decades later, it was reclassified as a subspecies of the black-tailed jackrabbit, L. californicus altamirae. Despite its ecological, social and economic importance of the jackrabbits, there is a gap in the knowledge of many species, such as L. altamirae, since historically few individuals have been sighted, collected and studied. On October 13, 2016 and September 22, 2021, 2 lagomorphs with straw-grayish fur as well as elongated limbs and ears was photographed in situ during the surveillance of wildlife in the lowlands of the Huasteca Potosina region, northeastern San Luis Potosí. Due to its coloration, morphological characteristics, and distribution, they were identified as L. altamirae. These are the first documented records of the species in the lowlands of the Huasteca Potosina, and the first records after a century of the species description. The closest known records are located ca. 98 km east in the state of Tamaulipas. The presence of the Tamaulipas white-sided jackrabbit in the region could be related to land use change. Systematic monitoring is necessary to improve knowledge about the distribution of this and other mammals in the lowlands of the Huasteca Potosina.